2016
DOI: 10.1007/s11664-016-4694-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxidation Temperature on Physical and Electrical Properties of Sm2O3 Thin-Film Gate Oxide on Si Substrate

Abstract: Thermal oxidation of 150-nm sputtered pure samarium metal film on silicon substrate has been carried out in oxygen ambient at various temperatures (600°C to 900°C) for 15 min and the effect of the oxidation temperature on the structural, chemical, and electrical properties of the resulting Sm 2 O 3 layers investigated. The crystallinity of the Sm 2 O 3 films and the existence of an interfacial layer were evaluated by x-ray diffraction (XRD) analysis, Fouriertransform infrared (FTIR) spectroscopy, and Raman ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 51 publications
(55 reference statements)
3
22
1
Order By: Relevance
“…The attained dielectric constants for all the anodised samples range from 8.11 to 10.30. However, these obtained values are lower as compared with the reported literature values of ∼15 [14,[18][19][20][21][22][23][24][25]. This might be due to the extremely high value of Q eff , STD, D it , and D total , charges are trapped in Si metal, IL and less charge are transmitted to the Al gate, and thus the dielectric values are lower as compared with the literature values.…”
Section: Resultscontrasting
confidence: 61%
See 2 more Smart Citations
“…The attained dielectric constants for all the anodised samples range from 8.11 to 10.30. However, these obtained values are lower as compared with the reported literature values of ∼15 [14,[18][19][20][21][22][23][24][25]. This might be due to the extremely high value of Q eff , STD, D it , and D total , charges are trapped in Si metal, IL and less charge are transmitted to the Al gate, and thus the dielectric values are lower as compared with the literature values.…”
Section: Resultscontrasting
confidence: 61%
“…and the smallest grain size with the average of 1.55 Å. The grain size of the cubic-Sm 2 O 3 can be obtained through Scherrer equation [23,24]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, the stability of the aqueous solution (pH value) is important to determine the solution reactions and structural transformation in aqueous phase method [23,[35][36][37]. In our previous work, the as-prepared In(OH) 3 NPs were synthesised at different pH values via co-precipitation method and their structure properties were investigated [38]. It was found that the smallest size of as-prepared In(OH) 3 NPs (∼11 nm) with maximum stability (3.6 mV) were synthesised at pH 10 through co-precipitation method.…”
Section: Introductionmentioning
confidence: 99%
“…High permittivity dielectrics (high-) are nowadays extensively studied as a replacement of silicon dioxide in various microelectronics devices [1][2][3][4], like gate dielectrics [5], memory devices [6], and so forth.…”
Section: Introductionmentioning
confidence: 99%